2019
DOI: 10.1364/josab.36.001117
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index profile tailoring of multimode optical fibers for the spatial and spectral shaping of parametric sidebands

Abstract: We introduce the concept of spatial and spectral control of nonlinear parametric sidebands in multimode optical fibers by tailoring their linear refractive index profile. In all cases, the pump experiences Kerr self-cleaning, leading to a bell-shaped profile close to the fundamental mode. Geometric parametric instability, owing to quasi-phase-matching from the grating generated via the Kerr effect by pump self-imaging, leads to frequency multicasting of beam self-cleaning across a wideband array of sidebands. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Spatial beam self-cleaning has also been reported in active multimode optical fibers even in the case of a non-parabolic refractive-index profile [17][18]22]. However, our experiments show that a deviation from a perfect parabolic shape increases the power threshold for beam cleaning, and consequently reduces the amount of power transferred to the "cleaned" mode [23]. Therefore, besides the choice of the input conditions, the principal ingredients for beam selfcleaning are the fiber characteristics, including the refractive index profile, the core diameter and the nonlinear refractive index of the glass.…”
Section: µMsupporting
confidence: 51%
“…Spatial beam self-cleaning has also been reported in active multimode optical fibers even in the case of a non-parabolic refractive-index profile [17][18]22]. However, our experiments show that a deviation from a perfect parabolic shape increases the power threshold for beam cleaning, and consequently reduces the amount of power transferred to the "cleaned" mode [23]. Therefore, besides the choice of the input conditions, the principal ingredients for beam selfcleaning are the fiber characteristics, including the refractive index profile, the core diameter and the nonlinear refractive index of the glass.…”
Section: µMsupporting
confidence: 51%
“…In 5,6 , the results of studies of the approach to the formation of the required profile are presentedusing its nonlinear induced correction at the end of the optical fiber (OF). Initially, this is the standard optical fiber (with a standard refraction index profile).…”
Section: Analysis Of Known Approaches To the Practical Implementation...mentioning
confidence: 99%
“…It should be noted that the approach presented in 5,6 concerns only the end of the OF, and, moreover, refers not to 3D, but to 2D structures. So, according to the publications considered, there are currently no recommendations and methods for manufacturing a 3D profile in the general case.…”
Section: Analysis Of Known Approaches To the Practical Implementation...mentioning
confidence: 99%
“…Recently, Krupa et al have demonstrated that both spatial and spectral control of GPI sidebands can be also achieved by tailoring the fiber refractive index profile. Namely, the presence of a dip into the refractive index profile of a GRIN MMF permits to change the spatial content of spectral sidebands from the fundamental into HOMs [17].…”
Section: Frequency Conversionmentioning
confidence: 99%